(untitled) (Kronika Bydgoska, 2017)
The National Secret Archives in Berlin-Dahlem (Geheimes Staatsarchiv Preußischer Kulturbesitz in Berlin-Dahlem) was of key importance for the studies on the history of Bydgoszcz when it was annexed by Prussia. One of the collections stored in it features an extensive list of sources to the history of Bydgoszcz in 1772-1806. This article presents the structure and contents of its manuscripts.